Literatur Review: Efektivitas Jahe Dan Kunyit Untuk Menurunkan Dismenore Pada Remaja - Safriana, Rizka Esty; Mulyani, Endah (Universitas Muhammadiyah Gresik, 2023)
Teenagers have more activities, start from school until extracurricular activities. Often pain during menstruation or dysmenorrhea interferes with their activities. Primary dysmenorrhea often occurs in young women, but this can be avoided by several methods, both pharmalogival and non-farmacological. One way to reduce dysmenorrhea is by consuming herbal drinks such as ginger and turmeric. The purpose of this study was to determine the effectiveness of consuming ginger and turmeric to reduce primary dysmenorrhea in young women. This research method is a literature review using an electronic database, namely Google Scholar, Dimensions, and ScienDirect. sSearch using three keywords “dysmenorrhea’, “ginger” and “turmeric”. The result found six articles for review. Four of them stated that ginger was more effective than turmeric in reducing primary dymenorrhea.